Determination of ethylene glycol in lubricants by derivatization static headspace gas chromatography. Issue 13 (11th June 2015) - Gras, Kaelyn; Luong, Jim; Lin, Monica; Gras, Ronda; Shellie, Robert A.
Abstract : A practical and reliable method for the analysis of ethylene glycol in either hydrocarbon based or synthetic lubricants has been successfully developed and implemented. Abstract : A practical and reliable method for the analysis of ethylene glycol in either hydrocarbon based or synthetic lubricants has been successfully developed and implemented. The method involves the use of static headspace gas chromatography and flame ionization detection. A fast and specific derivatization approach was incorporated, involving the use of phenyl boronic acid to convert ethylene glycol to 2-phenyl-1, 3, 2-dioxaborolane. With this analytical approach, a complete analysis can be conducted in less than 15 min with a relative precision of less than 10% at two concentrations; 100 ppm (w/w) and 1000 ppm (w/w) respectively. The method has a linear range from 5 ppm (w/w) to 1000 ppm (w/w) with a correlation co-efficient of 0.9993, a recovery greater than 95% and a detection limit of 1 ppm (w/w).